Resilience Reinforced: an In-Depth Analysis of Bank Syariah Indonesia’s Post-Merger Performance - Lestari, Sari; Mutmainah, Siti (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
The merger of Bank Syariah Indonesia was deemed appropriate as a strategic endeavor aimed at enhancing corporate resilience and fostering economic recuperation in the aftermath of the pandemic. This study endeavors to assess the performance of Bank Syariah Indonesia subsequent to a two-year period post-merger. The evaluation entailed a comparative analysis of the bank’s performance before and after the merger, employing metrics such as non-performing financing (NPF), financing to deposit ratio (FDR), return on assets (ROA), capital adequacy ratio (CAR), operating cost on operating income (BOPO), and net-operating margin (NOM). This study employs quantitative approach, utilizing secondary data. The source data, derived from the official Bank Syariah Indonesia (BSI) website, comprises financial and annual reports the years 2015 to 2022. The study also compares the performance to Bank Umum Syariah (BUS) based on sharia banking statistics derived from Otoritas Jasa Keuangan (OJK) website. The mann whitney test was applied to analyze the data, aiming to determine whether there was a significant difference in the performance of sharia banks after the merger compared to before the merger. The results show that there is a significant difference in the performance of the reviewed banks for NPF, ROA, CAR, BOPO, and NOM but not for FDR. The performance in all variables is on upward trajectory. Enhancements in bank performance indicate a favorable impact of mergers on the sharia banking sector. This research forms lays the groundwork for further exploration into the best practices of managing bank mergers.